Diet with decreased content of fermentable oligo-, diand monosaccharides and polyols (low FODMAP-diet) in treatment of irritable bowel syndrome - I. L. Khalif; I. A. Tishaeva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of review. To present the literature data on efficacy of the diet with decreased content of fermentable oligo, di and monosaccharides and polyols (low FODMAP diet) for irritable bowel syndrome (IBS) treatment. Summary. The role of fermentable carbohydrates in development of IBS symptoms is discussed, the basic principles of low FODMAPdiet, its advantage and shortcomings are reviewed. Conclusion. Shortchain carbohydrates cause increased colonic gas production, influence large intestinal motility, exert osmotic effect that promotes development of IBS symptoms. Low FODMAPdiet reduces symptom severity and can be applied for IBS treatment.